Case report: Successful treatment of a thallium sulfate intoxication in a dog with use of Prussian blue - McDermott, Fergal M.; Kan, Anne A.; Hunault, Claudine C.; Robben, Joris H.; de Lange, Dylan W.; Dijkman, Marieke A. (Frontiers in Veterinary Science, 2025)
Soluble thallium salts are highly toxic, with mortality rates exceeding 70% in animals compared to 6%−15% in humans. Early identification of thallium intoxicated patients and decreasing the toxic load by targeted treatment using Prussian Blue are associated with a better outcome in humans. Prussian blue, however, is rarely available or used in veterinary settings. Here we present a rare report of the successful use of Prussian Blue in the management of a dog with a thallium intoxication. A 5-year-old miniature Schnauzer, ingested a thallium sulfate based rodenticide leading to lethargy, anorexia, regurgitation, abdominal pain, borborygmi, constipation, ataxia, dermatitis and progressive alopecia. Intervention involved supportive care with subcutaneous fluids, carprofen, butylscopolamine and dexamethasone in combination with targeted treatment using the chelating agent Prussian blue (15 days) followed by activated charcoal (4 days). The serum thallium concentration on the 5th day of the Prussian Blue treatment was 196 mcg/L confirming thallium intoxication. The serum thallium concentrations were 20.7 mcg/L and 21.5 mcg/L on days 14 and 34 of treatment, respectively. The calculated elimination half-life during the during PB treatment was 2.8 days. The patient showed gradual improvement over several weeks, achieving full recovery at 11 weeks. This case emphasizes the importance of a timely diagnosis and the early start of targeted therapy using Prussian blue, in the management of thallium intoxication in veterinary patients.